Benthic Respiration in Hypoxic Waters Enhances Bottom Water Acidification in the Northern Gulf of Mexico. Issue 10 (16th October 2020) - Wang, Hongjie; Lehrter, John; Maiti, Kanchan; Fennel, Katja; Laurent, Arnaud; Rabalais, Nancy; Hussain, Najid; Li, Qian; Chen, Baoshan; Scaboo, K. Michael; Cai, Wei‐Jun
Abstract: It is known that surface water eutrophication enhances bottom water ocean acidification via respiration in coastal oceans. However, the role of benthic processes in influencing bottom water acidification has not been sufficiently explored. We examined this issue by analyzing a 10‐year summer carbonate chemistry dataset in bottom water together with recent benthic flux measurements and literature benthic flux data in the northern Gulf of Mexico. The difference between the observed and estimated pH (Ω) values calculated from anthropogenic CO2 increase and water column aerobic respiration were defined as ΔpH (ΔΩ). We found that ΔpH and ΔΩ values in hypoxic condition were −0.03 ± 0.04 (mean ± standard deviation) and −0.15 ± 0.39, respectively. Both ΔpH and ΔΩ values in hypoxic conditions were significantly lower than zero ( p  < 0.05). The net results of anaerobic respiration, oxidation of reduced chemcials, burial of iron sulfide minerals, and possible CaCO3 dissolution may have led to an alkalinity to DIC production ratio of less than 1 in porewater. This caused the ratio of alkalinity to dissolved inorganic carbon fluxes from sediment to bottom water to be less than 1, which led to additional bottom water acidification. Our analysis and model simulations demonstrate that severe hypoxic and anoxic conditions, which correspond to less water movement, favor the accumulation of benthic respiration products, leading to additional pH and Ω reductions. The findings on sediment processes contributing to acidification in bottom waters provide new insights into the sensitivity of coastal ocean acidification to low‐oxygen conditions under current and future climates and anthropogenic nutrient loading scenarios. Plain Language Summary: The ongoing decrease in seawater pH as a result of uptake of anthropogenic carbon dioxide (CO2 ) from the atmosphere is known as ocean acidification, which can be enhanced by oxygen‐consuming respiration in the water column. Meanwhile, regions of coastal hypoxia (dissolved oxygen <2 mg L −1 or 63 μmol L −1 ) have increased in size and number during the last several decades because of water column eutrophication. Previous studies take only the anthropogenic CO2 intrusion and aerobic respiration (respiration that consumes oxygen) into consideration when predicting the water column pH and carbonate mineral saturation. However, we found that anaerobic respiration (respiration that does not consumes dissolved oxygen) and the subsequent alkalinity removal via metal‐sulfide burials in sediments can further decrease pH and carbonate mineral saturation. Therefore, the bottom water acidification states are more aggravated in hypoxic conditions than previous estimations in the northern Gulf of Mexico. To our knowledge, this is the first study that uses data from multiple years and systematically examines the role of benthic fluxes on ocean acidification in eutrophic coastal bottom waters. The finding has profound implications for similar coastal systems where eutrophication‐induced bottom ocean acidification is likely more severe than we used to think. Key Points: Observed pH and Ω in hypoxic water in the nGoM are lower than those estimated from anthropogenic CO2 increase and organic carbon respiration The lower pH and Ω values are caused by neglecting benthic anaerobic respiration Benthic anaerobic respiration and subsequent alkalinity removal further increase the susceptibility of coastal waters to ocean acidification